Antimony susceptibility of Leishmania isolates collected over a 30-year period in Algeria. - Naouel Eddaikra; Khatima Ait-Oudhia; Ihcen Kherrachi; Bruno Oury; Farida Moulti-Mati; Razika Benikhlef; Zoubir Harrat; Denis Sereno (Public Library of Science (PLoS), 2018)
In Algeria, the treatment of visceral and cutaneous leishmanioses (VL and CL) has been and continues to be based on antimony-containing drugs. It is suspected that high drug selective pressure might favor the emergence of chemoresistant parasites. Although treatment failure is frequently reported during antimonial therapy of both CL and VL, antimonial resistance has never been thoroughly investigated in Algeria. Determining the level of antimonial susceptibility, amongst Leishmania transmitted in Algeria, is of great importance for the development of public health policies.Within the framework of the knowledge about the epidemiology of VL and CL amassed during the last 30 years, we sampled Leishmania isolates to determine their susceptibility to antimony. We analyzed a total of 106 isolates including 88 isolates collected between 1976 and 2013 in Algeria from humans, dogs, rodents, and phlebotomines and 18 collected from dogs in France. All the Algerian isolates were collected in 14 localities where leishmaniasis is endemic. The 50% inhibitory concentrations (IC50) of potassium antimony tartrate (the trivalent form of antimony, Sb(III)) and sodium stibogluconate (the pentavalent form of antimony, Sb(V)) were determined in promastigotes and intramacrophage amastigotes, respectively. The epidemiological cutoff (ECOFF) that allowed us to differentiate between Leishmania species causing cutaneous or visceral leishmaniases that were susceptible (S+) or insusceptible (S-) to the trivalent form of antimony was determined. The computed IC50 cutoff values were 23.83 μg/mL and 15.91 μg/mL for VL and CL, respectively. We report a trend of increasing antimony susceptibility in VL isolates during the 30-year period. In contrast, an increase in the frequency of S- phenotypes in isolates causing CL was observed during the same period. In our study, the emergence of S- phenotypes correlates with the inclusion of L. killicki (syn: L. tropica) isolates that cause cutaneous leishmaniasis and that have emerged in Algeria during the last decade.Our results provide insight into the spatiotemporal dynamics of Leishmania antimony susceptibility in Algeria. We highlight the need for the future implementation of an effective methodology to determine the antimony susceptibility status of Leishmania isolates to detect the emergence of and prevent the dissemination of drug-resistant strains.